2012 report on the health of Colorado's forests: forest stewardship through active management - Duda, Joseph, author; Halford, Meg, author; Lockwood, Ryan, author; Marcus, Naomi, author; Pfohl, Benjamin, author; Rogers, Kelly, author; Rossiter, GayLene, author; Tansey, Matt, author; Ciesla, William M., author; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2013)
The theme of this year's report is "Forest Stewardship through Active Management," with an emphasis on the link between healthy forests and sound forest management efforts. This is the 12th consecutive year we have produced a report on the state of Colorado's forests and actions we are taking to mitigate forest health concerns. This report provides an overview of the current condition of Colorado's forests and the recent activity of various insects and diseases. It demonstrates how responsible forest management - from wildfire risk mitigation around a single residence to the maintenance of large-scale watersheds - can be achieved. It also provides examples of how active forest management and stewardship will help ensure that Colorado's forests continue to provide all the benefits we enjoy.
Forest stewardship through active management
2012 Colorado forest health report
The reports describes "an annual investigation of critical forest health issues, including the identification of priority areas across the state where current forest conditions demand timely action." They are intended to "expand Coloradans' knowledge of and interest in our state's forest resources."
Reports produced by the Colorado State Forest Service in conjunction with Colorado Department of Natural Resources, Division of Forestry.
January 2013.
Keywords: forests and forestry; measurement; Colorado; forest health; forest management; forest stewardship